Stiffness Reduction Factor for LRFD of Columns - Harichandran, Ronald S. (Engineering Journal, 1991)
The stiffness reduction factors (SRFs) given in Table A of the LRFD Manual1 has an error that needs to be corrected. The error occurs in adopting the technique originally proposed by Yura in the context of ASD to LRFD. It is well known that when using the standard alignment charts to determine the effective length factor K of a column, the restraint factors G should reflect the inelastic behavior of the column.